LncRNA Expression in CD4+ T Cells in Neurosyphilis Patients - Liu, Li-Li; Zhu, Shao-Gang; Jiang, Xiao-Yong; Ren, Jun; Lin, Yong; Zhang, Ning-Ning; Tong, Man-Li; Zhang, Hui-Lin; Zheng, Wei-Hong; Fu, Hua-Jun; Luo, Hai-Juan; Lin, Li-Rong; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Recent studies have shown that several long noncoding RNAs (lncRNAs) are involved in regulating the immune response to cope with pathogenic invasion. To date, the roles of lncRNAs in the CD4+ T cell response to Treponema pallidum (T. pallidum) infection in neurosyphilis patients remain unknown. The mRNA and lncRNA expression profiles of CD4+ T cells that were isolated from neurosyphilis patients and healthy controls were analyzed by microarray. A total of 2258 lncRNAs and 1728 mRNAs were identified as over-expressed or under-expressed, respectively (fold change > 1.5) in the CD4+ T cells of neurosyphilis patients compared to the healthy controls. The lncRNA-mRNA co-expression network showed that 59 lncRNAs showed significant differences along with significantly different mRNAs. Among the 59 gene pairs, the LOC79999 mRNA was positively correlated with the RP11-160E2.16, RP11-160E2.11, and RP11-160E2.19 lncRNAs, and the NKX1-1 mRNA was positively correlated with the RP11-1398P2.1, RP11-160E2.19, and XLOC_003422 lncRNAs. The following five mRNAs were correlated with two differential lncRNAs: DUSP16, AP000349.1, FAM115C, TIMM8A, and SMCHD1. Gene Ontology(GO) analysis revealed that the differentially expressed coding genes were mainly involved in biological processes and the top 4 terms that associated with above-mentioned differentially expressed coding genes were as follows: defense response to fungus, defense response to bacterium, killing of cells of other organism and disruption of cells of another organism. A subsequent pathway analysis was also conducted, and several pathways, including the T cell receptor, MAPK, and TGF-beta signaling pathways, were associated with the differentially expressed mRNAs. This study reveals the differential expression profiles of lncRNAs in the CD4+ T cell response to the T. pallidum infection in neurosyphilis patients. LncRNAs are involved in key biological processes that comprise the CD4+ T cell response to the T. pallidum infection.